Mass Spectrometry Future Perceptions and Applications - Shamrao Kamble, Ganesh (IntechOpen, 2019)
This book provides a comprehensive overview of the emerging techniques and applications of mass spectrophotometry in various fields of sustainable chemistry. At the current level of development, the book provides "real-life" examples of analyses and applications. All the chapters are written by internationally recognized authors, and present qualitative and quantitative applications of mass spectrometry. These multidisciplined chapters cover the fundamentals as well as recent advanced analytical techniques, and offer significant information for various researchers studying biomedical, pharmaceutical, and environmental analysis.